Pengaruh Pemberian Azolla microphylla Dalam Pakan Terhadap Bobot Yolk, Albumen Dan Kerabang Telur Puyuh (Coturnix-Coturnix Japonica) - Putri, Cundha Pandita Fibula; Roesdiyanto, Roesdiyanto; Sulistyawan, Ibnu Hari (ANGON: Journal of Animal Science and Technology, 2019)
Backgrounds. The Effect of Addition Azolla microphylla in Feed to Weight of Yolk, Albumen and Eggshell of Quail ( Coturnix-coturnix japonica) is an experimental which conducted to investigate the effects of the addition of the Azolla microphylla meal in feed toward Weight of Yolk, Albumen and Eggshell. Materials and Methods. The materials used in this experiment were 100 female quail (Coturnix- coturnix japonica) of 30 days old. The treatment consisted R0 = basal feed without Azolla meal, R1 = basal feed + 1% of Azolla meal, R2 = basal feed + 2% of Azolla meal and R3 = basal feed + 3% of Azolla meal. The experiment method was used in vivo and was designed with Completely Randomized Design with 4 treatments and 5 replications. The data was analyzed with analysis of variance. The measured variables are weight of albumen, yolk and eggshell. Results. The results obtained average weight of yolk 3,204 g with range between 3 , 08 g - 3,226 g, average weight of albumen 6,311 g with range between 6,186 - 6,472 g, and average of eggshells 1,119 g 1,054 g - 1,148 g. The results of analysis variance obtained that the addition of Azolla microphylla meal had no significant effect (p>0,05) towards weight of yolk, albumen and eggshells quail egg (Coturnix-coturnix japonica) during first period. Conclusion. It was concluded that addition of Azolla microphylla meal gave a relative same weight towards weight of albumen, yolk and eggshells.